SAE Technical Paper Series 2014
DOI: 10.4271/2014-32-0104
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Small Rotary SI/CI Combustion Engine

Abstract: This paper describes the development of small rotary internal combustion engines developed to operate on the High Efficiency Hybrid Cycle (HEHC). The cycle, which combines high compression ratio (CR), constant-volume (isochoric) combustion, and overexpansion, has a theoretical efficiency of 75% using air-standard assumptions and first-law analysis. This innovative rotary engine architecture shows a potential indicated efficiency of 60% and brake efficiency of >50%. As this engine does not have poppet valves an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The model can be used to calculate the flow rate of jet flow with an escape coefficient. If P 1 � P 2 , the gas flows from chamber 1 to chamber 2, and the mass flow rate Q 1 is positive, which can be expressed as shown in equation (15) If P 1 < P 2 , it can be indicated that gas flows from chamber 2 to chamber 1, and Q 1 is negative. For opening gap 2 of the piston ring, referring to the calculation model of opening gap 1.…”
Section: Leakage Model Of Chambermentioning
confidence: 99%
See 1 more Smart Citation
“…The model can be used to calculate the flow rate of jet flow with an escape coefficient. If P 1 � P 2 , the gas flows from chamber 1 to chamber 2, and the mass flow rate Q 1 is positive, which can be expressed as shown in equation (15) If P 1 < P 2 , it can be indicated that gas flows from chamber 2 to chamber 1, and Q 1 is negative. For opening gap 2 of the piston ring, referring to the calculation model of opening gap 1.…”
Section: Leakage Model Of Chambermentioning
confidence: 99%
“…14 Its piston motion inertia is small, and the movement is more stable compared with a reciprocating piston engine. 15 However, due to the small compression ratio and long combustion chamber, the Wankel engine's combustion efficiency is low, and its emission problem is a serious shortcoming. 12 Therefore, Shi et al used CFD to analyze the influence of the Wankel engine's hydrogen volume fraction and injection angle on combustion performance.…”
Section: Introductionmentioning
confidence: 99%
“…16) and SARM for drones and range extenders. LiquidPiston: a rotary engine, fourstroke of "X" architecture with intake and exhaust through rotor shaft [95][96][97][98] . The LiquidPiston's "X" architecture is a rotary engine that similar in some aspects to the Wankel.…”
Section: Fig 15 Small Rotary Engine Finite Model and Stress Distribmentioning
confidence: 99%
“…The XE combustion chamber can also be installed in a fixed housing with relatively shape-free choice, and over-expansion strokes can be easily realized by appropriately positioning the intake and exhaust ports [11]. A 70-hp water-cooled diesel engine was initially devised to verify XE operation and basic principles [12], and a 70-cc air-cooled gasoline engine was subsequently applied to a small cart [13]. Recent research has continued to improve durability, heat transfer performance, and sealing performance aimed at developing emergency engines (range-extenders) for generators, small aircraft, and electric vehicles [14,15].…”
Section: Introductionmentioning
confidence: 99%